Clinical Manifestations and Pathogenesis of Uveitis in Ebola Virus Disease Survivors. (3rd October 2018) - Yeh, Steven; Shantha, Jessica G.; Hayek, Brent; Crozier, Ian; Smith, Justine R.
ABSTRACT: In the wake of the international Ebola virus disease (EVD) outbreak from 2014 to 2016, thousands of EVD survivors are at-risk of ophthalmic manifestations, as well as systemic sequelae including arthralgias, abdominal pain, psychosocial stressors, and risk of viral persistence in immune-privileged organs. Ophthalmic manifestations in EVD survivors include a spectrum of disease ranging from anterior uveitis to panuveitis, which confers a high risk of vision impairment and blindness, particularly given the access and resource limitations for ophthalmic subspecialty care in West Africa. Clinical studies in EVD survivors, animal models of EVD and translational investigation, have provided early insight into eye disease pathogenesis. Specifically, ocular inflammation recently observed in EVD survivors is thought to involve direct viral infection, inflammation, and tissue edema. Future research is needed to understand the timing of uveitis onset and management strategies, including the role of antiviral and anti-inflammatory therapies.